Segmentation, Targeting and Positioning in Determining Product Purchasing Decisions - Hakim, Ikhwanul (Jurnal Ilmu Manajemen Advantage, 2023)
Segmentation, targeting and positioning strategies are a way of marketing strategy to face competition and more easily map out several market segments, targets to be addressed and product positions that have a special place in the minds of consumers. Meanwhile, the segments, targets and positions set are the strengths of the company so that they can serve all the needs of consumers and influence purchasing decisions. This study aims to determine and analyze whether segmentation, targeting and positioning influence the purchasing decisions of Vaseline products in Lumajang. The sampling technique in this study used incidental sampling, which is a sampling technique based on the chance to meet a researcher. A sample can be used if the person is found by chance and is suitable as a data source. The sample in this study were 60 respondents. While the data analysis techniques in this study used instrument tests, classical assumption tests, multiple linear regression tests, hypothesis testing and statistical tests with the SPSS 21 program. The results of this study indicate that segmentation, targeting and positioning have a significant effect simultaneously on purchasing decisions for Vaseline products in Lumajang. The segmentation strategy that has been set needs to be reconsidered so that sales will increase.